(untitled) (Research, Society and Development, 2021)
This study aims to analyze the relationship between anxiety and stress in the performance of dental students in evaluations under active methodology. It is characterized as cross-sectional and retrospective, with a quantitative approach developed through an electronic form, with 71 academics from the dentistry course using a participant identification form, the anxiety assessment beck inventory (BAI), and the stress perception form before, during and after the active methodology applied in their evaluations. A greater portion of students aged between 18 and 24 years (80.02%) was noticed, with between 1 and 3 hours of study a day (30.98%). As for the assessment of anxiety, a higher degree of moderate or severe anxiety (53.5%). However, in the analysis of the mean value attributed to stress, there was a predominance before and during the assessment, with a reduction after its completion (6.30±3.07; 6.73±2.85; and 3.42±3. 16, respectively). By establishing the correlation between the mean values ​​of perceived stress and anxiety levels, a positive, moderate and significant correlation was observed in the three evaluated moments (p<0.05) and a significant difference was also obtained between the stress values during (A) and after the evaluation (B) with the grade values ​​indicated by the students (A:[F(1,718) = 529.27; p> 0.037]; B:[F(10.24) = 569.7 ; p<0.001]). Therefore, the multifactorial perception of the influence on academic performance is reinforced, and stress and anxiety can be stimulants or blockers of this performance, and it is up to the teacher to use methodologies that encourage a result closer to the student’s learning reality.